ENDORSEMENT AGREEMENTS ON INSTAGRAM SOCIAL MEDIA RELATED TO ARTICLE 7 OF LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Dwi Atmoko (Journal Indonesia Law and Policy Review, 2022)
The development of this technology is increasingly making people think more and more change, especially in economic activity. The form of economic activity that is affected is buying and selling activities in obtaining income or income or profits. In this day and age, after the presence of social media, there are many marketing techniques that can be used. One of the new marketing techniques is endorsements. This endorsement agreement is made in written form on direct massage Instagram, and it is legal according to Article 1320 of the Civil Code. The research method is carried out by descriptive analysis, with the approach used is a normative juridical approach. The results show that the form of legal protection in the endorsement agreement is that if there is a default or the implementation is not in accordance with the agreement, the celebgram as a business actor must replace the goods that have been sent and replace the money that has been sent, but in practice it is the online shop that is harmed.